2018
DOI: 10.1371/journal.pone.0196518
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed microRNAs associated with changes of transcript levels in detoxification pathways and DDT-resistance in the Drosophila melanogaster strain 91-R

Abstract: Dichloro-diphenyl-trichloroethane (DDT) resistance among arthropod species is a model for understanding the molecular adaptations in response to insecticide exposures. Previous studies reported that DDT resistance may involve one or multiple detoxification genes, such as cytochrome P450 monooxygenases (P450s), glutathione S-transferases (GSTs), esterases, and ATP binding cassette (ABC) transporters, or changes in the voltage-sensitive sodium channel. However, the possible involvement of microRNAs (miRNAs) in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 99 publications
2
22
0
Order By: Relevance
“…The possibility that the reduced expression of miR-310s in 91-R may impact a range of other genes cannot be ruled out. Computational predictions suggest putatively regulated transcripts encode a broad range of proteins, including a subset with functional annotation suggesting roles in xenobiotic detoxification 21 . Thus, the role of miR-310s in the DDT resistance phenotype may be more complex, and a future genome-wide transcriptome analysis of miR-310s mimics injected Drosophila samples could potentially provide a precise and unbiased measure of impact on target transcripts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The possibility that the reduced expression of miR-310s in 91-R may impact a range of other genes cannot be ruled out. Computational predictions suggest putatively regulated transcripts encode a broad range of proteins, including a subset with functional annotation suggesting roles in xenobiotic detoxification 21 . Thus, the role of miR-310s in the DDT resistance phenotype may be more complex, and a future genome-wide transcriptome analysis of miR-310s mimics injected Drosophila samples could potentially provide a precise and unbiased measure of impact on target transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the potential involvement of Cyp4g1 , Cyp6g1 , and Cyp12d1 in DDT resistance in 91-R was demonstrated via independent RNA interface (RNAi)-mediated knockdown of transcripts using the transgenic Gal4/UAS-RNAi expression system, each resulting in increased susceptibility 10 . Moreover, differences in micro-RNA (miRNA) repression of P450 transcription or translation was implicated within the polygenic DDT resistance mechanism of 91-R 11 , 21 . However, relatively little is known regarding the precise mechanism(s) by which P450s are silenced by miRNAs or the downstream effects on response to xenobiotic exposure in Drosophila .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that overproduction of detoxification enzymes is an important mechanism for insecticide resistance and complex regulatory mechanisms are involved in the up‐regulated expression of resistance‐associated detoxification genes, such as cis ‐regulatory elements and/or trans ‐acting factors, microRNAs and GPCR signaling cascades . The up‐regulation of CYP6FU1 conferring deltamethrin resistance in Laodelphax striatellus involves multiple cis ‐regulatory elements .…”
Section: Discussionmentioning
confidence: 99%
“…During embryogenesis, DE miRNAs directly govern critical developmental events, whereas constitutively expressed miRNAs most likely fine tune and maintain the basal gene expression levels. 47,48 We have thus focused our analyses in the current study on DE miRNAs in the developing murine NT. Bioinformatic analyses utilizing IPA, miRDB and TargetScan databases revealed that several DE miRNAs target the mRNA products of a range of genes encoding members of the PCP pathway ( Table 2).…”
Section: Planar Cell Polarity Pathway and Neural Tube Developmentmentioning
confidence: 99%